2022
DOI: 10.1371/journal.pntd.0010342
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to multiple pathogens - serological evidence for Rift Valley fever virus, Coxiella burnetii, Bluetongue virus and Brucella spp. in cattle, sheep and goat in Mali

Abstract: An important problem for livestock production in Mali is occurrence of several infectious diseases. A particular challenge for control of pathogens that affect different species, especially in a system with mixed herds with cattle, sheep and goats. Therefore, this study aimed to investigate co-exposure with Rift Valley fever virus (RVFV), Coxiella burnetii, bluetongue virus (BTV) and Brucella spp. in different livestock species in mixed herds. With the exception of BTV these pathogens are also zoonotic. A retr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(25 reference statements)
0
5
1
Order By: Relevance
“…Analysis at the animal level showed that 127,542 (6.00%) of the dairy cows were truly seropositive with C. burnetii . The prevalence of antibodies in sera of tested animals was estimated at 7.06% (true seroprevalence 6%) and was lower than the 14.85% reported by Saglam and Sahin ( 39 ) in Turkey, 47.2% recorded in Hungary ( 10 ) and 55.3% noted in Mali ( 9 ). In Latvia, 27% of cows which aborted tested positive for the presence of C. burnetii antibodies ( 7 ).…”
Section: Discussioncontrasting
confidence: 60%
“…Analysis at the animal level showed that 127,542 (6.00%) of the dairy cows were truly seropositive with C. burnetii . The prevalence of antibodies in sera of tested animals was estimated at 7.06% (true seroprevalence 6%) and was lower than the 14.85% reported by Saglam and Sahin ( 39 ) in Turkey, 47.2% recorded in Hungary ( 10 ) and 55.3% noted in Mali ( 9 ). In Latvia, 27% of cows which aborted tested positive for the presence of C. burnetii antibodies ( 7 ).…”
Section: Discussioncontrasting
confidence: 60%
“…Among the primary consequences of this disease are infertility, fetal death, late-gestation abortion, and decreased cattle productivity [ 26 , 27 ]. It is becoming more and more evident that brucellosis poses a serious public health risk in many underdeveloped countries due to the rise in incidences of morbidity in both humans and animals [ 28 , 29 ]. It is possible for humans to become infected with the disease either by coming into direct contact with sick animals or by consuming contaminated milk and milk products [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 388 eligible articles, 183 were excluded for multiple reasons described in Figure 1. Finally, a total of 205 articles (629 data on prevalence and/or CFR) met the inclusion criteria for this systematic review (Abakar et al., 2014; Abdallah et al., 2016; Adamu, 2020; Adamu et al., 2021; Adesiyun et al., 2020; Ahmed et al., 2018, 2020; Alhaji, 2020; Andayi et al., 2014; Andriamandimby et al., 2010; Andriamandimby et al., 2018; Aradaib et al., 2013; Archer et al., 2011, 2013; Atuman et al., 2022; Ayari‐Fakhfakh et al., 2011; Ba et al., 2012; Baudin et al., 2016; Beechler et al., 2015; van den Bergh et al., 2022; Bett et al., 2019; Bird et al., 2008; Bisimwa et al., 2016; Bloland et al., 2010; Blomstrom et al., 2016; Bob et al., 2017, 2022; Bonney et al., 2013; Bosworth et al., 2016; Boushab et al., 2015, 2016; Boussini et al., 2013, 2014; Breiman et al., 2010; Budasha et al., 2018; Budodo et al., 2020; Bukbuk et al., 2014; Centers for Disease Control and Prevention 2007; Chambaro et al., 2022; Chengula et al., 2014; Chevalier et al., 2005, 2011; Cichon et al., 2021; Clements et al., 2019; Cook et al., 2017; Cosseddu et al., 2021; Di Nardo et al., 2014; Diallo et al., 2005; Dione et al., 2022; Dondona et al., 2016; Durand et al., 2003, 2020; Dutuze et al., 2020; Ebogo‐Belobo et al., 2022; Eckstein et al., 2022; El Bahgy et al., 2018; El Mamy et al., …”
Section: Resultsmentioning
confidence: 99%
“…The pooled RVF prevalence in humans was estimated to be 7.8% [95% CI = 6.2–9.6] based on a sample of 102,427 participants. RVF prevalence data displayed presented substantial heterogeneity among the studies ( I 2 = 99.0% [95% CI = 98.9–99.0], p < 0.0001) (Adamu et al., 2021; Ahmed et al., 2018, 2020; Andayi et al., 2014; Andriamandimby et al., 2010; Aradaib et al., 2013; Archer et al., 2011, 2013; Atuman et al., 2022; Baudin et al., 2016; van den Bergh et al., 2022; Bett et al., 2019; Bloland et al., 2010; Bob et al., 2017, 2022; Bonney et al., 2013; Bosworth et al., 2016; Boushab et al., 2015; Breiman et al., 2010; Budodo et al., 2020; Bukbuk et al., 2014; Chambaro et al., 2022; Cichon et al., 2021; Clements et al., 2019; Cook et al., 2017; Cosseddu et al., 2021; Dione et al., 2022; Durand et al., 2003; Eckstein et al., 2022; Enem et al., 2020; Faye et al., 2007; Fokam et al., 2010; Gray et al., 2015; Grolla et al., 2012; Grossi‐Soyster et al., 2017; Gudo, Lesko, et al., 2016; Gudo, Pinto, et al., 2016; Guillebaud et al., 2018; Hassan et al., 2020; Hassanain et al., 2010; Heinrich et al., 2012; Ibrahim et al., 2021; Labeaud et al., 2008; Labeaud, Muiruri, et al., 2011; Labeaud et al., 2015; Muiruri et al., 2015; Lagare et al., 2019; Lysholm et al., 2022; Macharia et al., 2010; Mahmoud & Ali, 2021; Makiala‐Mandanda et al., 2018; Marrama et al., 2005; Mease et al., 2011; Mohamed et al., 2019; Msimang et...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation